Supine is Superior to Prone Position in Treating the Distal Ureteral Calculi During Extracorporeal Shockwave Lithotripsy: An Updated Meta-Analysis: Supine versus prone position for UC - Lu, Haiyan; Wang, Jun; Han, Peixuan; Xu, Weizhen (Urology Journal, 2022)
Purpose: Although extracorporeal shockwave lithotripsy (SWL) has been confirmed to be effective in treating ureteral stone, a definitive conclusion on which patient’s position is the optimal option during SWL treatment remains unclear. We, therefore, performed this updated meta-analysis to further clarify it. Materials and Methods: PubMed, Embase, and Cochrane library were performed to capture all potentially eligible studies from their inception to October 2020. After screening eligible studies, extracting essential data, and assessing the risk of bias, we used STATA 14.0 to complete all statistical analyses. Results: We included 7 studies involving 8 cohorts in the final analysis. Our meta-analysis suggested that the prone position was inferior to the supine position in terms of stone fragmentation and stone clearance rate after completing the first treatment (95% CI: 0.30-0.63; OR = 0.44;), however, subgroup analysis indicated that the difference between supine and prone positions for stone fragmentation and the stone clearance rate was only getting statistical significance for distal ureteral stone (95% CI: 0.23-0.53; OR = 0.35). Moreover, subgroup analysis of two eligible randomized controlled trials suggested that the mean number of sessions per patient in the supine group was less than that in the prone group (95% CI: 0.11-0.48; WMD = 0.294). No major and severe complication was detected to be done with the association with positions. Conclusion: SWL of the supine position may be the preferred option because this strategy can increase the distal ureteral stone-free rate compared to the prone position.